DESCRIPTIVE STUDY OF FUNCTIONAL STATUS BREAST CANCER PATIENTS WITH CHEMOTHERAPY - Hartanti Dwi Rita; Wijiastuti Utari (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Chemotherapy can experience changes in functional status breast cancer patients. The purpose of this study was to describe the functional status of breast cancer patients with chemotherapy, with design uses descriptive analysis. The sample is all breast cancer patients with chemotherapy at RSUD Kraton Kabupaten Pekalongan. The respondents is 46, with sampling method used total sampling. The results of this study is 67.4% had an assessment of functional status in category A which meant that they were independent in 6 function including the functions of bathing, dressing, toileting, moving, continental and eating. 10.9% of respondents have functional status category F. 4.3% of respondents have functional status categories B, C, D, E, and G. Comprehensive nursing care is needed to improve the functional status of breast cancer patients with chemotherapy.